2013
DOI: 10.1371/journal.pone.0053971
|View full text |Cite
|
Sign up to set email alerts
|

Salt Content Impacts Food Preferences and Intake among Children

Abstract: Decreasing dietary sodium intake, which can be achieved by reducing salt content in food, is recommended. Salt contributes to the taste of foods and makes them more enjoyable. Whether a food is liked or disliked is an important determinant of food intake, especially among children. However, the role of salt in children's food acceptance has received little attention. The impact of salt content on children's hedonic rating and intake of two foods was investigated in children. Using a within-subject crossover de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 24 publications
(38 reference statements)
1
41
1
Order By: Relevance
“…It is common practice to add seasonings or salt to vegetables (Ahern et al., ; Birch, ; Drewnowski, ; Leshem, ; Martin et al., ). Enhancing saltiness by salt addition can suppress bitterness (Bouhlal et al., ; Bouhlal et al., ; Keast & Breslin, ; Mennella et al., ). On the contrary, Mojet et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is common practice to add seasonings or salt to vegetables (Ahern et al., ; Birch, ; Drewnowski, ; Leshem, ; Martin et al., ). Enhancing saltiness by salt addition can suppress bitterness (Bouhlal et al., ; Bouhlal et al., ; Keast & Breslin, ; Mennella et al., ). On the contrary, Mojet et al.…”
Section: Discussionmentioning
confidence: 99%
“…Soups containing MSG were perceived as saltier and more pleasant compared to soups without MSG, although no effect of MSG addition on savory taste was observed. Bouhlal, Chabanet, Issanchou, and Nicklaus () and Bouhlal, Issanchou, Chabanet, and Nicklaus () investigated the impact of salt content on vegetable liking and intake in children. Adding sodium chloride to green beans enhanced saltiness and suppressed bitterness which might be beneficial to increase vegetable intake in children (Bouhlal et al., ; Mennella, Pepino, & Beauchamp, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several examples were presented where labeling alone influences salt content preferences (13). Examples discussed included observations where reduced salt content was accepted (14) and could even become part of early learning and development of healthy food preferences (15). Public awareness campaigns to reduce salt intake have been demonstrated to be effective, using objective markers such as urine sodium measurements (16,17).…”
Section: Discussion Of State-of-the-sciencementioning
confidence: 99%
“…As for pair comparison, it was shown that 4-year-old children could not rank sweet solutions according to their perceived sweetness intensity, but were able to rank them according to their preferences (Liem et al ., 2004). However, intensity ranking was successfully applied to the study of salt perception in usual foods (green beans, pasta) with children aged 8-11 years (Bouhlal et al ., 2013), or to the study of the impact of sourness in fruit beverages with children aged 9-14 years (Kildegaard et al ., 2011b). Children aged 9-10 performed less well than teenagers (14-16 years) (de Graaf and Zandstra, 1999).…”
Section: Rankingmentioning
confidence: 99%